Vascular Injury in the Zebrafish Tail Modulates Blood Flow and Peak Wall Shear Stress to Restore Embryonic Circular Network - Baek, Kyung In; Chang, Shyr-Shea; Chang, Chih-Chiang; Roustaei, Mehrdad; Ding, Yichen; Wang, Yixuan; Chen, Justin; O'Donnell, Ryan; Chen, Hong; Ashby, Julianne W.; Xu, Xiaolei; Mack, Julia J.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Mechano-responsive signaling pathways enable blood vessels within a connected network to structurally adapt to partition of blood flow between organ systems. Wall shear stress (WSS) modulates endothelial cell proliferation and arteriovenous specification. Here, we study vascular regeneration in a zebrafish model by using tail amputation to disrupt the embryonic circulatory loop (ECL) at 3 days post fertilization (dpf). We observed a local increase in blood flow and peak WSS in the Segmental Artery (SeA) immediately adjacent to the amputation site. By manipulating blood flow and WSS via changes in blood viscosity and myocardial contractility, we show that the angiogenic Notch-ephrinb2 cascade is hemodynamically activated in the SeA to guide arteriogenesis and network reconnection. Taken together, ECL amputation induces changes in microvascular topology to partition blood flow and increase WSS-mediated Notch-ephrinb2 pathway, promoting new vascular arterial loop formation and restoring microcirculation.